All Days 2005
DOI: 10.2118/96507-ms
|View full text |Cite
|
Sign up to set email alerts
|

Exploration Drilling in the Barents Sea; Prevailing Zero Discharge Regime, Challenges and Learning From Recent Exploration Drilling

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe Barents Sea is an environmentally important ecosystem defined as part of the Arctic. The Norwegian environmental regulation is particular strict for this area, a zero discharge regime prevails. This paper describes the challenges of entering the area for exploration drilling. With reference to a recent operation (2005) a presentation of how the challenges were resolved is given. New procedures and new techniques were implemented to achieve compliance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, identifying cost-effective and efficient waste handling and management systems, which have a minimal environmental footprint, is one of the biggest challenges in the Arctic region (Paulsen et al, 2005). In addition, the operational performance of the chosen waste handling technologies or systems can be greatly influenced by the operating conditions of the Arctic region (Barabadi et al, 2015, Barabadi and.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, identifying cost-effective and efficient waste handling and management systems, which have a minimal environmental footprint, is one of the biggest challenges in the Arctic region (Paulsen et al, 2005). In addition, the operational performance of the chosen waste handling technologies or systems can be greatly influenced by the operating conditions of the Arctic region (Barabadi et al, 2015, Barabadi and.…”
Section: Introductionmentioning
confidence: 99%
“…The Canada Environmental Studies Research Fund (2004) prepared drilling waste management best practice, to provide a drilling sump options reference tool and to promote the proper management of drilling waste. Paulsen et al (2005) demonstrated the procedures for achieving zero discharge in the harsh operational conditions. The Norwegian Petroleum Safety Authority (PSA) has also developed rules and regulations for conducting petroleum activities in the Arctic region.…”
Section: Introductionmentioning
confidence: 99%